Double surfactants‐assisted electromembrane extraction of cyromazine and melamine in surface water, soil and cucumber samples followed by capillary electrophoresis with contactless conductivity detection. (6th November 2019) - Guo, Mengnan; Liu, Shiyu; Wang, Manman; Lv, Yifei; Shi, Jialei; Zeng, Yuan; Ye, Jiannong; Chu, Qingcui
Abstract: BACKGROUND: Cyromazine (CYR) and its main degradation product melamine (MEL) are attracting wide attention due to their potential hazards to the environment and humans. In this work, double surfactants‐assisted electromembrane extraction (DS‐EME) by Tween 20 and alkylated phosphate was firstly used for purification and extraction of CYR and MEL, and the extract was directly analyzed by capillary electrophoresis with capacitively coupled contactless conductivity detection. RESULTS: Under the optimum conditions, two targets could be well separated from the main interferences, including common biogenic amines and inorganic cations within 14 min. This developed method was successfully applied to the analyses of surface water, soil and cucumber samples, and the average recoveries were in the range 93.3–112%. DS‐EME provided a synergistic purification and enrichment effect for CYR and MEL by adding Tween 20 and alkylated phosphate into donor phase and supporting liquid membrane, respectively. Satisfactory limits of detection [0.2–1.5 ng mL −1, signal‐to‐noise ratio ( S/N ) = 3] could be obtained in the tested sample matrices, and the corresponding enrichment factors were up to 115∼123 times. CONCLUSION: This developed method provides an alternative for the simultaneous analysis of CYR and MEL in complex real‐world samples. © 2019 Society of Chemical Industry